SYNERGY OF WELFARE AND JOB SATISFACTION: TRANSFORMATION OF EMPLOYEE PERFORMANCE AMONG THE KITCHEN STAFF OF THE NUTRITION SERVICE UNIT (SPPG) AT SPPG JELUPANG 02, SOUTH TANGERANG CITY - Ading Sunarto; Zubair Nabiil Musyaffa Yusuf (Yayasan Education and Social Center, 2026)
Employee Performance Research is one of the important factors in supporting the success of an organization in achieving its goals. Employee welfare and job satisfaction are aspects that play a role in improving performance, especially in organizations engaged in nutrition fulfillment services. This study aims to analyze welfare and job satisfaction in improving employee performance in the Kitchen Staff of the Nutrition Fulfillment Service Unit (SPPG) Jelupang 02, South Tangerang City. The research uses a qualitative descriptive approach through interviews, observation, documentation, SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM) techniques. The results of the study show that employee well-being and job satisfaction make a positive contribution to improving employee performance. The results of the SWOT analysis placed SPPG Jelupang 02 in Quadrant I (Growth Strategy), which shows that the organization has greater strengths and opportunities than weaknesses and threats. QSPM analysis shows that the priority strategy to be implemented is to improve employee competencies through training programs and human resource development. Therefore, improving welfare, improving work facilities, strengthening communication, and developing competencies sustainably is expected to improve employee performance optimally.